Pengaruh Suhu dan Lama Penyimpanan Terhadap Stabilitas Warna dan Karakteristik Kolang-kaling dengan Penambahan Ekstrak Kayu Secang (Caesalpinia sappan L.) - Chandra Pratiwi, Ni Luh; Diah Puspawati, Gusti Ayu Kadek; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i03.p03, 2022)
“Kolang-kaling” is generally added with food coloring to make it look more attractive, one source of natural color that is safe for consumed comes from sappan wood. This study aimed to determine the effect of temperature and storage time on color stability and characteristics of “kolang-kaling” with the addition of extract sappan wood and to get the exact temperature and storage time to the maintenance color stability and the best characteristics of “kolang-kaling” with the addition of extract sappan wood. The experimental design used was a factorial randomized block design (RBD) with 2 factors. The first factor was temperature which consists of 3 levels (refrigerator temperature, room temperature and 400C). The second factor was the time of storage which consists of 4 levels (1 days, 3 days, 5 days, and 7 days). The treatment was repeated 2 times in order to obtain 24 experimental units. The data obtained were analyzed using analysis of variance and if the treatment had an significant effect on the test parameters, then continued with the Duncan Multiple Range Test (DMRT). The results showed that interaction of the temperature and storage time had a very significant effect on color intensity, total anthocyanin, hedonic of color, hedonic of aroma, hedonic of texture, overall acceptance, scoring of color, scoring of aroma, and scoring of texture. Refrigerator temperature and storage for 1 days was the best treatment to maintain the colorant stability and characteristic of the “kolang-kaling” extract sappan wood with the color intensity of 0.70, value L* 23.8, a* 47.4, b* 57.8, total anthocyanin 10.79 mg/100g, pH 6.0, antioxidant activity 77,0%, also sensory evaluation color was red and liked, aroma was typical of “kolang-kaling” and liked, texture was slightly chewy and liked, and overall acceptance was liked.